Enhancement of Soft Skills Competence in Human Resources as a Key Success Factor in the Digital Business Era - Karneli, Okta; Handayati, Ratna; Rijal, Syamsu (ADMAN: Journal of Contemporary Administration and Management, 2024)
With the ongoing development of digital technology, the business landscape is undergoing a significant paradigm shift. Digital transformation has altered the way companies operate, communicate, and engage with customers. In the digital business era, a company's success is not solely determined by technical expertise but also by the individual's ability to manage interpersonal relationships. The objective of this research is to analyze the enhancement of soft skills competence in human resources as a primary success factor in the digital business era. This research adopts a descriptive qualitative literature review method utilizing primary data sources from scholarly articles identified through Google Scholar. The study will conduct a thorough analysis of relevant and current literature published between 2017 and 2023. The findings indicate that human resources with a strong portfolio of soft skills become valuable assets to a company. Effective communication, collaboration skills, and proficient leadership form the foundation for team productivity and success. Leaders capable of guiding through change and possessing a strategic vision will steer the company toward long-term success.